1995
DOI: 10.1002/ijc.2910640513
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the precursor of gelatinase A/72 kda type IV collagenase/MMP‐2 in lung carcinomas correlates with the expression of membrane‐type matrix metalloproteinase (MT‐MMP) and with lymph node metastasis

Abstract: We have identified a novel membrane-type matrix metalloproteinase (MT-MMP) expressed on the cell surface and inducing activation of pro-gelatinase A in vitro. In this study, we further examined the possibility that MT-MMP is the activator of pro-gelatinase A in tumors as well as in vitro. Expression of MT-MMP mRNA was analyzed by Northern blotting in 58 cases of human lung carcinomas. MT-MMP mRNA expression was increased in tumor tissues compared with adjacent normal tissues. The ratio of MT-MMP mRNA levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
153
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(162 citation statements)
references
References 17 publications
7
153
0
2
Order By: Relevance
“…Immunoreactivity for MMP-2 was correlated significantly with Masaoka clinical stage, and MMP-2 expression was correlated with the degree of malignant behavior of the thymoma and may be an indicator for distinguishing invasive thymoma from noninvasive thymoma. MMP-2 protein reportedly is correlated with poor prognostic variables in a variety of malignancies, such as breast, 15,16 lung, 17,18 stomach, 19 and head and neck carcinomas. 20 It was long been believed that TIMPs suppressed tumor invasion by inhibiting MMPs in experimental and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity for MMP-2 was correlated significantly with Masaoka clinical stage, and MMP-2 expression was correlated with the degree of malignant behavior of the thymoma and may be an indicator for distinguishing invasive thymoma from noninvasive thymoma. MMP-2 protein reportedly is correlated with poor prognostic variables in a variety of malignancies, such as breast, 15,16 lung, 17,18 stomach, 19 and head and neck carcinomas. 20 It was long been believed that TIMPs suppressed tumor invasion by inhibiting MMPs in experimental and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…MT1-MMP is overexpressed in malignant tumor tissues, including lung and stomach carcinomas that contain activated gelatinase A. This suggests that MT1-MMP is associated with the activation of progelatinase A in these tumor tissues [14,16,17]. MT1-MMP expression has been detected in HT-1080 cells treated with TPA and MDA-MB-231 cells stimulated with concanavalin A, which induce progelatinase A activation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…1363-1371 © 2001 Cancer Research Campaign doi: 10.1054/ bjoc.2001.1806, available online at http://www.idealibrary.com on http://www.bjcancer.com aminoterminal domain for the expression of activity (Tryggvason et al, 1987). The urokinase type plasminogen activator (uPA) -plasmin system (Mazzieri et al, 1997) and membrane type MMP-1 (MT1-MMP, MMP-14) (Sato et al, 1994;Tokuraku et al, 1995) have been suggested to represent physiological mechanisms for the control of MMP-2 and MMP-9 activity. Recent studies have shown that human trypsin-2 is more potent than plasmin and other serine proteinases in activating several MMPs, including MMP-2 and MMP-9 (Sorsa et al, 1997), and that downregulation of trypsin-2 expression and activity in colon cancer cells is associated with decreased proMMP-9 activation (Lukkonen et al, 2000).…”
mentioning
confidence: 99%